Copper current collector based on SnPc-COF modification layer, preparation method of copper current collector and application of copper current collector in anode-free lithium metal battery

By using the copper current collector with the SnPc-COF modified layer in an anode-free lithium metal battery, the battery performance problem caused by high reactivity between lithium and current collector is solved, and the uniform deposition and peeling of lithium are achieved, which extends the cycle stability and Coulomb efficiency of the battery.

CN119650568AActive Publication Date: 2025-03-18NINGBO JIERONG NEW MATERIALS CO LTD +1

Patent Information

Application Number
CN202411811752.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

Due to the high reactivity between lithium and current collector, existing anode-free lithium metal batteries lead to irreversible lithium consumption, excessive electrolyte decomposition, unfavorable and fragile interface of solid electrolyte, which in turn leads to low Coulomb efficiency and shortened cycle life.

Method used

The copper current collector based on the SnPc-COF modified layer was used to dissolve SnPc-COF and PAN in N-methylpyrrolidone, forming a precursor liquid and coating it on copper foil. After vacuum drying, a 2μm-thick SnPc-COF modified layer was prepared to improve the deposition and peeling behavior of lithium.

Benefits of technology

Through the use of the SnPc-COF modified layer, the uniform deposition and peeling of lithium are significantly improved, the cycle stability and Coulomb efficiency of the battery are extended, and the higher energy density and longer cycle life are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650568A_ABST
    Figure CN119650568A_ABST
Patent Text Reader

Abstract

The invention provides a copper current collector based on a SnPc-COF modification layer, a preparation method of the copper current collector and application of the copper current collector in an anode-free lithium metal battery, tin phthalocyanine COF (SnPc-COF) is modified on the copper current collector to serve as an artificial modification layer of the anode-free battery current collector to improve deposition and stripping behaviors of lithium, and the thickness of the modification layer is only 2 microns. A phthalocyanine polymer skeleton is rich in N atoms, has a strong adsorption effect with lithium ions, and can be used as a channel for uniform transmission of the lithium ions; and meanwhile, Sn < 4 + > in phthalocyanine and lithium ions form a Li-Sn alloy during lithium deposition, so that the nuclear potential of lithium is reduced, and uniform deposition of lithium is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anode-free batteries, and in particular relates to a copper current collector based on a SnPc-COF modified layer, a preparation method thereof, and an application thereof in an anode-free lithium metal battery. Background Art

[0002] The rapid development of portable electronics, electric vehicles, and smart grids has greatly driven the demand for high-capacity renewable energy storage systems. However, existing lithium-ion batteries can no longer meet this demand. Lithium metal batteries (LMBs) with lithium metal as the negative electrode have attracted much attention due to their ultra-high theoretical specific capacity (3860mAh / g). Compared with traditional graphite negative electrodes, their energy density can be increased by about 50%.

[0003] However, the high reactivity between organic electrolytes and lithium metal limits the practical application of lithium metal anodes, resulting in irreversible lithium consumption and excessive decomposition of electrolytes, which in turn forms an unfavorable and fragile solid electrolyte interface (SEI) and promotes the growth of lithium dendrites, ultimately leading to low Coulombic efficiency and shortened cycle life. In order to compensate for the deactivated lithium and obtain better cycle stability, ultra-thick lithium metal anodes are used in LMBs reported in the literature, and their lithium content exceeds 10 times the actual demand. However, this will cause a huge waste of lithium resources and seriously damage the actual energy density of LMBs, making them unusable for practical batteries. In this regard, anode-free LMBs use lithium-free current collectors and are considered to be the batteries that can achieve the highest energy density. Anode-free LMBs use copper (Cu) or other non-lithium-based substrates as the anode, and lithium ions are extracted from the cathode material and deposited on the anode during battery charging. However, due to the limited lithium source and the incompatibility of the substrate, anode-free lithium batteries usually form a large number of lithium dendrites and "dead lithium", as well as continuous side reactions with the electrolyte, resulting in rapid capacity decay of the battery.

[0004] In order to improve the cycle stability of anode-free lithium batteries, many strategies have been proposed, among which the interface modification of the artificial SEI layer of the current collector is considered to be one of the most effective strategies. It is well known that the deposition of lithium on the negative electrode goes through three processes: 1) lithium ions pass through the SEI layer to reach the negative electrode surface; 2) lithium ions are reduced to nuclei on the negative electrode surface; 3) the aggregation and growth of crystal nuclei. The first two processes are crucial for uniform lithium deposition. However, most researchers in the current work on anode-free artificial interface layers only focus on one of the processes. If only the lithium flux is changed, the nucleation process on the current collector is still not easy, and the weak adsorption force with the current collector is still easy to cause the growth of dendrites. Only using alloys to change the nucleation wettability of lithium metal cannot ensure the uniform lithium flux near the anode, and lithium alloys will inevitably contact the electrolyte to form a fragile SEI layer, which is also unfavorable. Therefore, in order to truly solve the problem of anode-free lithium dendrites, it is far from enough to focus on only one process. It is best to combine the two strategies. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a copper current collector based on a SnPc-COF modified layer.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0009] SnPc-COF and PAN are dissolved in N-methylpyrrolidone at a mass ratio of 3 to 6:1 to obtain a precursor solution with a SnPc-COF concentration of 0.02 to 0.08 mmol / mL;

[0010] The precursor solution is coated on the copper foil and then vacuum dried to obtain a copper current collector based on the SnPc-COF modified layer.

[0011] As a preferred solution of the method for preparing the copper current collector based on the SnPc-COF modified layer of the present invention, wherein: the coating rotation speed of the precursor solution is 1000-1500 r / s.

[0012] As a preferred embodiment of the method for preparing the copper current collector based on the SnPc-COF modified layer of the present invention, the vacuum drying is carried out at a drying temperature of 50 to 80° C. and for a drying time of 10 to 12 hours.

[0013] As a preferred embodiment of the method for preparing a copper current collector based on a SnPc-COF modified layer of the present invention, the method for preparing SnPc-COF comprises:

[0014] 1,2,4,5-tetracyanobenzene and tin tetrachloride are dissolved in ethylene glycol in a mass ratio of 2 to 5:1, and ultrasonically mixed and uniformly added with 2 to 6 wt % of a catalyst compared to the amount used in the reaction system, and ultrasonically mixed until a milky white solution is formed;

[0015] The milky white solution was placed in a microwave reactor for microwave reaction to generate dark green powder, which was then reflux-washed using a Soxhlet extractor to obtain SnPc-COF.

[0016] As a preferred solution of the method for preparing the copper current collector based on the SnPc-COF modified layer of the present invention, the temperature of the microwave reaction is 160-200° C. and the time is 15-25 min.

[0017] Another object of the present invention is to provide a copper current collector based on a SnPc-COF modified layer.

[0018] Another object of the present invention is to provide an application of a copper current collector based on a SnPc-COF modified layer in the preparation of an anode-free lithium metal battery.

[0019] Another object of the present invention is to provide an anode-free lithium metal battery.

[0020] In order to solve the above technical problems, the present invention provides the following technical solution: including using a copper current collector based on a SnPc-COF modified layer as an anode.

[0021] As a preferred solution of the anode-free lithium metal battery of the present invention, the copper current collector based on the SnPc-COF modified layer is pre-plated with lithium.

[0022] As a preferred embodiment of the anode-free lithium metal battery of the present invention, the anode-free lithium metal battery uses lithium iron phosphate LiFePO4 as the cathode active material.

[0023] Beneficial effects of the present invention:

[0024] The present invention modifies tin phthalocyanine COF (SnPc-COF) onto the copper current collector as an artificial modification layer of the anode-free battery current collector to improve the deposition and stripping behavior of lithium. The thickness of the modification layer is only 2 μm. The phthalocyanine polymer skeleton is rich in N atoms and has a strong adsorption effect on lithium ions, which can serve as a channel for uniform transmission of lithium ions. At the same time, Sn in phthalocyanine 4+ During lithium deposition, it forms Li-Sn alloy with lithium ions, which reduces the nucleation potential of lithium and is beneficial to the uniform deposition of lithium. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0026] Figure 1 This is the FT-IR spectrum of SnPc-COF prepared in Example 1 of the present invention.

[0027] Figure 2 This is the XRD spectrum of SnPc-COF prepared in Example 1 of the present invention.

[0028] Figure 3 This is the SEM image of SnPc-COF prepared in Example 1 of the present invention.

[0029] Figure 4 This is the SEM-EDS image of SnPc-COF prepared in Example 1 of the present invention.

[0030] Figure 5 This is a surface SEM image of SP-Cu prepared in Example 1 of the present invention.

[0031] Figure 6 This is a cross-sectional SEM image of the SP-Cu prepared in Example 1 of the present invention.

[0032] Figure 7 Surface and cross-sectional SEM images of Cu after lithium plating.

[0033] Figure 8 Surface and cross-sectional SEM images of the SP-Cu after lithium plating prepared in Example 1 of the present invention.

[0034] Fig. 9 The volt-ampere cycle curve of the symmetrical battery assembled after pre-lithiation of the present invention.

[0035] Fig.10 This is a cycle performance diagram of the Li / / Cu half-cell of the present invention.

[0036] Fig.11 This is the cycle stability diagram of SP-Cu-Li / / Li-SP-Cu of the present invention.

[0037] Fig.12 This is the cycle stability diagram of the SP-Cu-Li / / LFP full battery of the present invention.

[0038] Fig.13 The performance comparison of Li / / Cu half-cells prepared with different SnPc-COF concentrations in the precursor solution of Example 2 of the present invention is shown.

[0039] Fig.14 The electrochemical performance of Li / / Cu half-cells assembled with Cu current collectors with different modified layers prepared in Example 1 and Comparative Examples 2 to 4 is compared. DETAILED DESCRIPTION

[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0041] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0042] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0043] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.

[0044] In the present invention, when the current collector is subjected to performance testing, it is assembled into a half-cell or a full-cell. Specifically, the battery is assembled according to the following method:

[0045] Preparation of cathode electrode sheet:

[0046] 10 wt.% polyvinylidene fluoride (PVDF) was weighed into a 5 mL sample bottle, and NMP was added until PVDF was fully dissolved into a colorless, transparent, and thick liquid; 80 wt.% lithium iron phosphate LiFePO4 (LFP) powder and 10 wt.% conductive carbon black (Super P) were weighed and fully ground, and then the mixed powder was transferred to a glass sample bottle containing 5 mL of colorless, transparent, and thick liquid. After being dispersed by magnetic stirring for 12 hours, the slurry was poured on an aluminum foil current collector, and the active material loading was prepared by adjusting the scraper scale matched by the MSK-AFA-1 type coater. About 2.5 mg cm -2 The electrode pieces were vacuum dried at 80℃ for 1000min and then cut into circular electrode pieces with a diameter of 12mm, which were used as LFP cathode electrode pieces.

[0047] Assemble the battery:

[0048] Half-cell:

[0049] Assembled in a CR2025 type coin cell, the coin cell consists of a lithium foil with a diameter of 14 mm, a glass fiber separator, 80 μL of an electrolyte (1 M LiTFSI, DOL:DME=1:1 vol%) and a Cu current collector to obtain a Li / / Cu battery;

[0050] The assembled battery was placed at 60 °C for 10 h to fully activate the battery, and then the charge and discharge tests were performed on a battery tester (Land CT2001A). The charge and discharge current density was 1 mA cm -2 , discharge for 1h, and charge to 0.1V.

[0051] Full Battery:

[0052] Pre-plated 5 mAh cm on Cu / Cu current collector -2 The capacity of lithium is then assembled with the LFP cathode into a solid-state battery, which is cycled at 0.5C in the range of 2.5 to 4V to test the cycle stability of the anode-free battery.

[0053] Example 1

[0054] This embodiment provides a method for preparing a SnPc-COF modified copper current collector, specifically:

[0055] 1) Synthesis of SnPc-COF:

[0056] 0.3563 g 1,2,4,5-tetracyanobenzene (TCBN) and 0.1 g tin tetrachloride were dissolved in 20 ml ethylene glycol, and ultrasonically mixed. Then 0.8 ml catalyst 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) was added, and ultrasonically mixed for 15 min until a milky white solution was formed.

[0057] The milky white solution was placed in a microwave reactor and reacted at 180°C for 15 min. The generated dark green powder was then refluxed and washed using a Soxhlet extractor for two days to obtain SnPc-COF.

[0058] Figure 1 This is the FT-IR spectrum of SnPc-COF. It can be seen that the original raw material is located at 2246.37cm -1 The cyano peak disappeared and the peak at 1649.98 cm appeared in the reaction product. -1 The stretching vibration peak of the C=N bond and the CN bond are located at 1316.23 cm -1 and 1064.47cm -1 The bending and stretching vibration peaks indicate that tetracyanobenzene reacted successfully and polymerized to form phthalocyanine COF.

[0059] The structure of SnPc-COF was analyzed by powder X-ray diffraction (PXRD). Figure 2 As shown, it can be seen that the XRD spectrum shows an obvious small-angle diffraction peak at around 8.42°, which is a characteristic signal of COF, indicating that it has an ordered layered stacked two-dimensional (2D) structure, which is conducive to the formation of vertical lithium ion transmission channels and promotes the short-range effective transport of lithium ions.

[0060] The morphology, size and element distribution of SnPc-COF were studied by SEM. Figure 3 As shown, SnPc-COF appears as irregular solid particles as a whole, and the synthesized solid particles are relatively uniform in size, about 1 μm.

[0061] Then, SnPc-COF was subjected to EDS elemental analysis. Figure 4 It can be seen from the mapping diagram that Sn and N elements are evenly distributed, which also proves the synthesis of SnPc-COF.

[0062] 2) Preparation of SnPc-COF@Cu (SP-Cu):

[0063] 20 mg SnPc-COF and polyacrylonitrile (PAN) were dissolved in 1 ml N-methylpyrrolidone at a mass ratio of 4:1 and mixed evenly to prepare a precursor solution with a SnPc-COF concentration of 0.04 mmol / mL;

[0064] The precursor solution was coated on the copper foil using a spin coater at a rotation speed of 1500 r / s. The coated copper foil was placed in a vacuum oven and dried at 80° C. for 12 h to obtain SnPc-COF@Cu.

[0065] Figure 5 The surface SEM image of SP-Cu is shown in Figure 2. Figure 5In the figure, we can see that the original brown-red copper foil surface is covered with green phthalocyanine. Through SEM, we can observe the surface of the copper foil after modification by local magnification. We can see that the copper foil surface is covered with coating, and SnPc-COF is wrapped in PAN, which evenly covers the copper foil surface. SP-Cu is cut and trimmed, and its cross section is observed. The results are as follows: Figure 6 As shown, Figure 6 The SEM image clearly shows that there is a 2μm thick coating on the copper surface, which also proves the successful coating of the modification layer.

[0066] Comparative Example 1

[0067] This comparative example uses bare copper (Bare Cu) without any modification as a comparison.

[0068] The SnPc-COF@Cu of Example 1 and the bare copper of Comparative Example 1 were assembled into half-cells and full-cells for performance testing. Before the test, 5 mAh cm -2 The surface and cross-sectional morphologies of the lithium were observed by SEM to illustrate the lithium deposition. Figure 7 , Figure 8 As shown, from Figure 7 From the planar SEM image, it can be seen that the lithium on the bare Cu is loose ribbon-shaped lithium, which indicates that the adsorption energy between Cu and lithium is not high, so lithium cannot be deposited evenly and tightly on the copper. Such deposition often leads to the formation of dendrites or even dead lithium. However, the lithium on SnPc-COF@Cu is densely deposited on the copper with almost no gaps. Figure 8 It can also be seen that lithium is deposited under the coating, which shows that lithium ions are deposited through the modified layer. The coating is crucial for the uniform transmission and deposition of lithium ions. Comparing the thickness of the lithium layer on SnPc-COF@Cu and bare Cu, the lithium deposited on SnPc-COF@Cu is also thinner and more dense, indicating that the successful modification of SP-COF coating on copper foil has improved the problem of poor compatibility between copper foil and lithium.

[0069] Fig. 9 The CV curve shows the kinetic behavior of Li deposition / dissolution on Cu. It can be seen that the current response of the SnPc-COF@Cu electrode is significantly increased, showing fast charge transfer and reversible reaction kinetics. Therefore, the presence of the SnPc-COF@Cu coating can lead to fast and uniform charge transfer. This will promote the uniform deposition of lithium ions on copper.

[0070] Assembled into Li / / Cu half-cell for performance testing. Generally speaking, anode-free batteries have limited lithium sources, so the coulombic efficiency decays quickly. Fig.10It was found that the coulombic efficiency of bare copper decayed very quickly, and it could only stably cycle for about 20 cycles, and the coulombic efficiency would decay to near 0 in less than 50 cycles. This is because copper has poor wettability to lithium, and it is easy to form dendrites and dead lithium during the process of lithium deposition and stripping, and the deposited lithium easily reacts with the electrolyte to consume a large amount of electrolyte. However, using the modified SP-Cu current collector, it can stably cycle for more than 400 cycles, and the coulombic efficiency is above 99%. This shows that the SP-COF coating greatly improves the deposition and stripping of lithium.

[0071] The SP-Cu current collector / bare copper is pre-lithiated and assembled into a full cell (symmetrical cell) Li / / SP-Cu Fig.11 From the test results of SPCu-Li / / Li-SP-Cu symmetric batteries, it can be seen that the symmetric battery assembled with SP-Cu current collector can be stably cycled for more than 2000 hours, indicating good stability during lithium deposition and stripping.

[0072] Fig.12 The capacity of the bare Cu-assembled anode-free full battery decays very quickly, decaying rapidly in the first 50 cycles, and the capacity decay is close to 0 by the 100th cycle. However, the capacity curve of the full battery assembled with SP-Cu current collector remains stable after 170 cycles, and the capacity retention rate is above 85%. This shows that the modified SP-Cu current collector greatly improves the lithium compatibility of Cu foil, making long-term stable cycling of anode-free batteries possible.

[0073] Example 2

[0074] The difference between this embodiment and embodiment 1 is that the concentration of the precursor solution in step 2) is adjusted. Specifically, the concentration of SnPc-COF in the precursor solution is adjusted to 0.02, 0.04, 0.06, and 0.08 mmol / mL, respectively.

[0075] The remaining steps were all referred to Example 1 to obtain copper current collectors with different concentrations of modified layers in this comparative example, which were assembled into Li / / Cu half-cells to compare the electrochemical performance. The results are as follows: Fig.13 shown.

[0076] from Fig.13It can be seen that when the SnPc-COF precursor concentration is 0.02mmol / mL, the Li / / Cu battery can stably cycle about 175 cycles. When the SnPc-COF concentration increases to 0.04mmol / mL, the stability of the battery is further improved, and it can stably cycle more than 270 cycles. However, when the concentration is increased, the stability of the battery decreases. The Li / / Cu half-cell prepared with SnPc-COF precursor solutions with concentrations of 0.06mmol / mL and 0.08mmol / mL can only cycle about 100 and 50 cycles, respectively. This proves that the modified layer on the Cu foil should not be too thick, otherwise its conductivity will deteriorate and affect the performance of the battery.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 1 is that only Sn 4+ Modify the Cu current collector, specifically:

[0079] Tin tetrachloride was dissolved in N-methylpyrrolidone and mixed evenly to prepare a precursor solution with a concentration of 0.04mmol / mL;

[0080] The precursor solution was coated on the copper foil using a spin coater at a speed of 1500 r / s. The coated copper foil was placed in a vacuum oven at 80 °C and dried for 12 h to obtain Sn 4+ -Cu.

[0081] Comparative Example 3

[0082] The difference between this comparative example and Example 1 is that only phthalocyanine COF is used to modify the Cu current collector, specifically:

[0083] 1,2,4,5-Tetracyanobenzene (TCBN) was dissolved in N-methylpyrrolidone and mixed evenly to prepare a precursor solution with a concentration of 0.04 mmol / mL;

[0084] The precursor solution was coated on the copper foil using a spin coater at a rotation speed of 1500 r / s. The coated copper foil was placed in a vacuum oven at 80° C. and dried for 12 h to obtain Pc-Cu.

[0085] Comparative Example 4

[0086] The difference between this comparative example and Example 1 is that only PAN is used to modify the Cu current collector, specifically:

[0087] Polyacrylonitrile (PAN) was dissolved in N-methylpyrrolidone and mixed evenly to prepare a precursor solution with a concentration of 0.04 mmol / mL;

[0088] The precursor solution was coated on the copper foil using a spin coater at a rotation speed of 1500 r / s. The coated copper foil was placed in a vacuum oven at 80° C. and dried for 12 h to obtain PAN-Cu.

[0089] The Cu current collectors with different modified layers prepared in Comparative Examples 2 to 4 were assembled into Li / / Cu half-cells, and their electrochemical performance was measured. Fig.14 As shown, it can be seen that bare copper (Bare Cu) without any modification layer can only stably cycle about 20 cycles, and the coulomb efficiency drops rapidly after 40 cycles. The performance of copper foil modified with only tin ions and phthalocyanine COF without metal is slightly improved, and its coulomb efficiency can be stabilized at about 98% before 80 cycles, and becomes extremely unstable after 80 cycles. The copper foil modified with PAN can only stably cycle for 180 cycles. The copper foil modified with tin phthalocyanine and binder PAN has the best performance and can stably cycle for more than 400 cycles.

[0090] Therefore, it can be concluded that it is not enough to have only one of the metal or polymer in the modification layer. With only metal ions, the alloy formed is still not stable enough and will react with the solution at the interface to form a fragile SEI layer. With only polymer coating, it can only prevent direct contact with the solution and accelerate the transmission of lithium ions, but it cannot regulate the nucleation behavior, and the deposition of lithium ions on copper is still uneven. Only the synergy of metal ions and polymers can achieve the best effect.

[0091] In summary, the present invention modifies tin phthalocyanine COF (SnPc-COF) onto the copper current collector as an artificial modification layer of the anode-free battery current collector to improve the deposition and stripping behavior of lithium. The thickness of the modification layer is only 2 μm. The phthalocyanine polymer skeleton is rich in N atoms, which has a strong adsorption effect on lithium ions and can serve as a channel for uniform transmission of lithium ions. At the same time, Sn in phthalocyanine 4+ During lithium deposition, it forms Li-Sn alloy with lithium ions, which reduces the nucleation potential of lithium and is beneficial to the uniform deposition of lithium.

[0092] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a copper current collector based on a SnPc-COF modified layer, characterized in that: The method comprises dissolving SnPc-COF and PAN in N-methylpyrrolidone at a mass ratio of 3 to 6:1 to obtain a precursor solution having a SnPc-COF concentration of 0.02 to 0.08 mmol / mL; The precursor solution is coated on the copper foil and then dried in vacuum to obtain a copper current collector based on the SnPc-COF modified layer.

2. The method for preparing a copper current collector based on a SnPc-COF modified layer according to claim 1, characterized in that: The coating rotation speed of the precursor solution is 1000-1500 r / s.

3. The method for preparing a copper current collector based on a SnPc-COF modified layer according to claim 1, characterized in that: The vacuum drying has a drying temperature of 50 to 80° C. and a drying time of 10 to 12 hours.

4. The method for preparing a copper current collector based on a SnPc-COF modified layer according to claim 1, characterized in that: The preparation method of SnPc-COF comprises: 1,2,4,5-tetracyanobenzene and tin tetrachloride are dissolved in ethylene glycol in a mass ratio of 2 to 5:1, and ultrasonically mixed and uniformly added with 2 to 6 wt % of a catalyst compared to the amount used in the reaction system, and ultrasonically mixed until a milky white solution is formed; The milky white solution was placed in a microwave reactor for microwave reaction to generate dark green powder, which was then reflux-washed using a Soxhlet extractor to obtain SnPc-COF.

5. The method for preparing a copper current collector based on a SnPc-COF modified layer according to claim 5, characterized in that: The temperature of the microwave reaction is 160-200° C., and the time is 15-25 min.

6. A copper current collector based on a SnPc-COF modified layer prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the copper current collector based on the SnPc-COF modified layer as claimed in claim 6 in the preparation of an anode-free lithium metal battery.

8. An anode-free lithium metal battery, characterized in that: The copper current collector based on the SnPc-COF modified layer as claimed in claim 6 is used as the anode.

9. The anode-free lithium metal battery according to claim 8, characterized in that: The copper current collector based on the SnPc-COF modified layer is pre-plated with lithium.

10. The anode-free lithium metal battery according to claim 8, characterized in that: The anode-free lithium metal battery uses lithium iron phosphate LiFePO4 as the cathode active material.

Citation Information

Patent Citations

  • Modified lithium battery negative electrode as well as preparation method and application thereof

    CN113991060A

  • A method for preparing a phthalocyanine-type single-atom catalyst

    CN114931966A

  • Negative-electrode-free lithium metal battery based on sulfonic-group-modified covalent organic framework material

    CN116344828A

  • Nano-fluid effect enhanced lithium negative electrode artificial interface layer as well as preparation method and application of nano-fluid effect enhanced lithium negative electrode artificial interface layer

    CN118630148A

  • Negative-electrode-free pole piece and preparation method thereof

    CN118738272A

Cited By

  • Biomass hard carbon sodium ion battery negative electrode material as well as preparation method and application thereof

    CN120413663A